Microstructural characterization of pressureless sintered silver die attached material - Esa, Siti Rahmah (2022)
Sintered silver (Ag) is one of the most promising interconnect materials for high power electronics applications due to its ability to withstand high temperature exceeding 250 °C while in operation.In this thesis, themicrostructural evolutions of spherical and flake types pressureless sintered Ag die attached material was characterized at different sintering temperatures. The interface between flake sintered Ag and copper(Cu) substrate was examined to understand the factor that affects its bonding quality. The flakesintered Ag was exposed to corrosive environment to study the effect of corrosion to its properties change. The microstructural characterization was performed by means of field emission scanning electron microscopy (FESEM), focused ion beam (FIB) and high resolution transmission electron microscopy (HRTEM). The elemental and chemical states analysis were performed via energy dispersive spectroscopy (EDS), x-ray photoelectron spectroscopy (XPS) and time of flight secondary ion mass spectrometry (TOF-SIMS). The mechanical properties was conducted using dynamic microhardness tester and the electrical conductivity was measured using hall effect instrument. The result shows that the evolutions of spherical particles occur as the contact area is formed, followed by neck formation via atomic diffusions leading to the formation of solid Ag network. The flake particles shows self-produced nano particles that accelerates the sintering process and it has a higher tendency for particle diffusions due to larger surface area per thickness ratio.The improvement in conductivity was observed as compared with unsintered Ag particles. The flake Ag particle sintered at 300 °C shows an increase in elastic modulus and hardness as compared to unsintered Ag particle. The investigation at the interface between sintered Ag and Cu substrate shows an indication of interface diffusion after the sintering process. However, the growth of Cuoxide layer at Ag-Cu interfaces induce negative effects due to the formation of voids and separations in between Cu and Cu oxide interface. Finally, the evidence of corroded sintered Ag joint was observed after exposure to the corrosive environment. The Cu oxide layer with delamination between Cu and Cu oxide interface initiate a weak point and further enhance the corrosion effect. The corrosion and delamination will result in product failure due to poor mechanical strength of the corroded joints.In conclusion, sintering temperature plays an important role in the microstructural change of sintered Ag joint. The knowledge gained from this study would be beneficial in the application of pressureless sintered Ag die attached material in semiconductor packaging process.